Digitalisasi Umkm: Menggali Potensi Pasar Lokal Melalui Optimalisasi E-Commerce - Dea Armasari; Salsabillah Rahmawati; Najma Wardatun Nadya; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This Community Service Program (PKM) aims to enhance the understanding of students at SMA Pelita Bangsa and MSME actors regarding the importance of digitalization through the use of e-commerce. Digitalization is considered a strategic step to expand markets, improve business efficiency, and strengthen the competitiveness of local products in the digital economy era. The program was carried out through digital literacy training, hands-on practice, and technical assistance. The results show that students gained new knowledge about digital business, although challenges such as limited skills, internet access, and capital still exist. With the support of schools, the government, and the younger generation, MSME digitalization can serve as a real solution for local economic development and fostering an entrepreneurial spirit among youth.